The Influence Of Management Accounting System On Managerial Performance In The DPRD Of South Sulawesi Province - Afifah Junianti Triyanto; Khadijah Darwin; Indriana (International Journal of Economic Research and Financial Accounting, 2024)
This research aims to determine the influence of the Management Accounting System on Managerial Performance in the DPRD of South Sulawesi Province. The method used in this research is a quantitative method obtained from questionnaires distributed and linked to the problem being studied. The population in this study were employees of the DPRD of South Sulawesi Province. The sample in this study was 100 respondents using the Slovin formula. Data collection was carried out by distributing questionnaires and the data source used was primary data. The research instrument used in this research used the Likert scale method. Data was processed using the IBM SPSS V.25 application. The data analysis technique in this research uses simple linear regression analysis. The research results show that the management accounting system has a positive and significant effect on managerial performance with a significance value of 0.000 (<0.05). So it can be concluded that the management accounting system is the for achieving managerial performance